2013
DOI: 10.1055/s-0033-1341477
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of a New Immediate-release Compound Omeprazole Capsule and its Comparison with the Enteric-coated Formulation under Fasting and Fed Conditions

Abstract: The present study was conducted to describe the pharmacokinetic profile of immediate-release compound omeprazole capsule and compare it with the enteric-coated formulation under fasting and fed condition.This study was designed to phase I, open-label, randomized, 3-part clinical trial. 12 subjects in part one received single doses (20 mg and 40 mg) and repeated doses (20 mg). Different 30 subjects in part 2 (fasting condition) and part 3 (fed condition) received either compound omeprazole capsule (40 mg) or de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
2
6
1
Order By: Relevance
“…Similar results were shown in another study conducted in healthy volunteers in both fasted and fed conditions (Z. Liu et al, 2013). This is better reflected by the in vitro drug release results in pH 6.8 mHanks buffer than phosphate buffer, as the former reveals the difference in drug release profiles between the tested PPI products as well as the variation in drug release in the six dissolution test repetitions of the same product (as shown by the higher standard deviation in tlag, t80 and release rate).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar results were shown in another study conducted in healthy volunteers in both fasted and fed conditions (Z. Liu et al, 2013). This is better reflected by the in vitro drug release results in pH 6.8 mHanks buffer than phosphate buffer, as the former reveals the difference in drug release profiles between the tested PPI products as well as the variation in drug release in the six dissolution test repetitions of the same product (as shown by the higher standard deviation in tlag, t80 and release rate).…”
Section: Discussionsupporting
confidence: 91%
“…The reported in vivo tmax values for omeprazole products range from 1.9 to 4.0 hours (K. Boussery et al, 2011;S. Karim et al, 2014;Z. Liu et al, 2013) and the in vitro t80 values are 0.9-1.3 and 1.2-2.2 hours in pH 6.8 phosphate buffer and mHanks buffer respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In our opinion, a low-fat breakfast would also influence PPI absorption, however, the effect might be less noticeable and maybe not clinically relevant. In this regard, the presence of food has been reported to reduce the C max and AUC of omeprazole [21] and esomeprazole [13]. Thomson et al found that the evening meal reduced the tenatoprazole AUC compared with evening administration of the drug under fasting conditions [14].…”
Section: Discussionmentioning
confidence: 99%
“…When capsules or powder for oral suspension were administered 1 h after a meal, both AUC and C max decreased by 24% and 63%, respectively [32]. Liu et al [34] performed a randomized, open-label study involving 30 healthy subjects who were given a single 40 mg IR omeprazole capsule (containing sodium bicarbonate) while fasting or with a standard meal. The meal consisted of two pieces of bread, two sausages, two eggs, 100 g of salad, and 250 mL of milk.…”
Section: Food Effectmentioning
confidence: 99%
“…After 7 days of each dosing regimen, significant changes were observed in the pharmacokinetic profiles of both DR products: not only C max decreased (by 58% and 63%), but AUC 0-12 also decreased (by 35% and 38%). Additionally, Liu et al [34] reported a negative effect of food on the AUC of DR omeprazole capsules.…”
Section: Food Effectmentioning
confidence: 99%